EFFICACY OF TELMISARTAN TO OTHER ANTI-HYPERTENSIVE DRUGS ON INSULIN SENSITIVITY (International Research Journal of Pharmacy, 2022)
Background: In individuals with hypertension and diabetes mellitus, elevated ET-1 (endothelin) levels and the existence of insulin resistance are important factors that lead to renal and cardiovascular complications. But in India, these subjects are not sufficiently studied.Aim: The objective is to compare the effectiveness of telmisartan with other widely used anti-hypertensive medications in terms of insulin sensitivity with respect to HOMA-IR in individuals with diabetic hypertension.Methods: 140 participants who reported to the Institute during the specified study period and had both diabetes and hypertension were evaluated. These subjects were split into two equal groups, with Group I subjects (n = 68) receiving telmisartan and Group II subjects (n = 72) receiving other antihypertensive medications for 12 weeks, including ramipril in 4 subjects, cilnidipine in 24 subjects, and amlodipine in 44 subjects. Change in insulin sensitivity on HOMA-IR was the primary outcome measured, and ET-1 levels were the secondary outcome.Results: At baseline, the median HOMA-IR levels were 3.9 (2.0-5.7) for telmisartan and 3.7 (2.9-5.7) for another group. When compared to other antihypertensive groups, telmisartan significantly reduced median HOMA-IR after 12 weeks of treatment (p=0.001). Comparable outcomes were observed for ET-1, whose levels dropped in both groups after 12 weeks with a non-significant difference and p=0.88.Conclusion: When compared to other antihypertensive medications, telmisartan dramatically increases insulin sensitivity after 12 weeks in individuals with type 2 diabetes and hypertension. ET-1 levels, however, showed a similar impact on endothelial function in both groups. Positive metabolic effects of telmisartan may aid in the management of macro and microvascular complications.